Recent advances in capillary electrophoresis‐mass spectrometry: Instrumentation, methodology and applications. Issue 1 (12th November 2018) - Stolz, Alexander; Jooß, Kevin; Höcker, Oliver; Römer, Jennifer; Schlecht, Johannes; Neusüß, Christian
Abstract: Capillary electrophoresis (CE) offers fast and high‐resolution separation of charged analytes from small injection volumes. Coupled to mass spectrometry (MS), it represents a powerful analytical technique providing (exact) mass information and enables molecular characterization based on fragmentation. Although hyphenation of CE and MS is not straightforward, much emphasis has been placed on enabling efficient ionization and user‐friendly coupling. Though several interfaces are now commercially available, research on more efficient and robust interfacing with nano‐electrospray ionization (ESI), matrix‐assisted laser desorption/ionization (MALDI) and inductively coupled plasma mass spectrometry (ICP) continues with considerable results. At the same time, CE‐MS has been used in many fields, predominantly for the analysis of proteins, peptides and metabolites. This review belongs to a series of regularly published articles, summarizing 248 articles covering the time between June 2016 and May 2018. Latest developments on hyphenation of CE with MS as well as instrumental developments such as two‐dimensional separation systems with MS detection are mentioned. Furthermore, applications of various CE‐modes including capillary zone electrophoresis (CZE), nonaqueous capillary electrophoresis (NACE), capillary gel electrophoresis (CGE) and capillary isoelectric focusing (CIEF) coupled to MS in biological, pharmaceutical and environmental research are summarized.